Clinical Diagnostics: Online SERS Quantification of Staphylococcus aureus and the Application to Diagnostics in Human Fluids (Adv. Mater. Technol. 8/2016). Issue 8 (10th November 2016) - Catala, Carme; Mir‐Simon, Bernat; Feng, Xiaotong; Cardozo, Celia; Pazos‐Perez, Nicolas; Pazos, Elena; Gómez‐de Pedro, Sara; Guerrini, Luca; Soriano, Alex; Vila, Jordi; Marco, Francec; Garcia‐Rico, Eduardo; et al.
Abstract : In article number 1600163, Ramon A. Alvarez‐Puebla and co‐workers combine surface‐enhanced Raman scattering encoded particles, biorecognition elements (aptamer/antibody) and microfluidics into a device for the optical detection of Staphylococcus aureus in human fluids. The bacteria quantification is achieved for short acquisition time (10 min mL −1 ) and at low concentration of S. aureus (<15 CFUs mL −1 ).